PENGARUH PENGEMBANGAN KARIR DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT SUMBER ALFARIA TRIJAYA, TBK DC PARUNG, BOGOR - Irna Triyunitha; Bambang Purnomo Yanuarso (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to determine the effect of career development on employee performance both partially, the effect of job satisfaction on employee performance partially, and simultaneously at PT Sumber Alfaria Trijaya, Tbk Parung Branch, Bogor. The research method used is quantitative with an approach. The sampling technique uses saturated sampling with a total of 100 employees. Data collection techniques are carried out through primary and secondary data. Data analysis techniques use the SPSS version 26 program. The analysis techniques used are validity testing, reliability testing, classical assumption testing, normality testing, multicollinearity testing, heteroscedasticity testing, simple linear regression analysis, multiple linear regression analysis, correlation coefficient testing, determination coefficient testing, and hypothesis testing. Partial hypothesis testing of variables using multiple linear regression. The results of the study show that: (1) Career development (X1) obtained t-count 5.839> t-table 1.661 with a significance of 0.000 <0.05, so that H₀ is rejected and H₁ is accepted. This means that career development (X1) has a significant effect on employee performance (Y) (2) Job satisfaction hypothesis test (X2) produces a t-count of 2.226> t-table 1.661 with a significance of 0.000 <0.05, so that H₀ is rejected and H₁ is accepted. This means that job satisfaction (X2) has a positive effect on employee performance (Y) (3) simultaneous hypothesis testing obtained an F-count value of 40.894> F-table 3.09 with a significance of 0.000 <0.05, so that H₀ is rejected and H₁ is accepted. This means that career development and job satisfaction variables have a significant effect simultaneously on employee performance. The determination obtained R Square of 0.457 means that career development and job satisfaction variables together have an influence of 45.7% on employee performance. While the remaining 54.3% is influenced by other factors not examined in this study.